2013
DOI: 10.1590/1414-431x20133003
|View full text |Cite
|
Sign up to set email alerts
|

Early responses of the STAT3 pathway to platinum drugs are associated with cisplatin resistance in epithelial ovarian cancer

Abstract: Cisplatin resistance remains one of the major obstacles when treating epithelial ovarian cancer. Because oxaliplatin and nedaplatin are effective against cisplatin-resistant ovarian cancer in clinical trials and signal transducer and activator of transcription 3 (STAT3) is associated with cisplatin resistance, we investigated whether overcoming cisplatin resistance by oxaliplatin and nedaplatin was associated with the STAT3 pathway in ovarian cancer. Alamar blue, clonogenic, and wound healing assays, and Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 37 publications
2
34
0
2
Order By: Relevance
“…Our observational findings combined with recent experimental investigations showing the involvement of STAT3 signaling in the induction of chemoresistance in EOCs 3840 suggest that germline STAT3 polymorphisms may influence sensitivity of EOCs to platinum-based therapy. Thus, for women newly diagnosed with EOC, STAT3 genotype status could possibly serve as a diagnostic marker of initial platinum resistance.…”
Section: Discussionsupporting
confidence: 72%
“…Our observational findings combined with recent experimental investigations showing the involvement of STAT3 signaling in the induction of chemoresistance in EOCs 3840 suggest that germline STAT3 polymorphisms may influence sensitivity of EOCs to platinum-based therapy. Thus, for women newly diagnosed with EOC, STAT3 genotype status could possibly serve as a diagnostic marker of initial platinum resistance.…”
Section: Discussionsupporting
confidence: 72%
“…These results partly explain CCL5-induced cisplatin resistance. We focused on the STAT3 signaling pathway, a member of STAT transcription factor family, given its significant role in tumorigenesis and regulation of chemotherapy resistance in cancer cells (17,18,42). Previous studies have demonstrated that STAT3 and CCL5 contribute to the maintenance of tamoxifen resistance in breast cancer, and STAT3 phosphorylation is constitutively activated and retained via CCL5 stimulation (3,9,43).…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 contributes to oncogenesis in many human cancers, including prostate, breast, nasopharyngeal carcinomas and ovarian cancers (15,16). STAT3 pathway activity has been associated with cisplatin resistance in human ovarian carcinomas (17). Furthermore, a previous study demonstrated that using small molecule inhibitors or interference RNA could rescue the inherent and acquired chemoresistance of ovarian cancer cells (18).…”
Section: Introductionmentioning
confidence: 99%
“…Results from another study by Yang et al [60], similar to those obtained by Maciejczyk et al [53] or Yi et al [58] showed that quercetin pretreatment at a low dose may augment drug-resistant ovarian cancer cells for cisplatin chemotherapy by involving the endoplasmic reticulum-stress (ERS) proces via alternation of STAT3 kinase signaling (phosphorylation), a key player involved in ovarian cancer [61,62], modulated by ERS [60]. In this study quercetin decreased the viability of both the C13 * and P-ris cells in a dosedependent manner, with an IC50 value of approximately 100 μM at 48 h; the growth of both cell types could only be significantly inhibited with quercetin concentrations >40 μM, with a negligible cytotoxicity in both cell types at a dose 20 μM.…”
Section: Chemoprotective Activities In Ovarian Cancer Cells Of Quercementioning
confidence: 54%